Relações entre argumentos jurídicos e argumentos morais - Nunes, Eduardo Brandão (2019)
Analyzes some of the main characteristics of legal arguments and moral arguments, presenting some relations between such argumentations. The aim is to analyze and describe some of the relations between these two types of argumentation in a theoretical manner. The main features and singularities of legal argumentation are first analyzed, exemplifying how some types of legal arguments can be represented through schemes. Then there is the analysis of moral arguments and some of their main characteristics and complexities. It is only after the description of these two types of argumentation that there are generalizations about their relations. For such aims, the bibliographic revision procedure is used, in a qualitative way, to understand the objects of study. It is understood that there are congruences between law and morals in the use of methods and structures to arrive at justifications for decisions or conclusions based on arguments that present reasons. The two types of arguments are not necessarily inseparable; they are both essential for life in society. And it is also noted that for a more adequate legal practice in the face of the demands of community life, it is necessary, to some extent, for morality to permeate the law, either through premises or moral arguments. In this way, it is also investigated to what extent this is necessary and in what terms this occurs, in the process being first necessary to understand the forms and methods of the arguments to be investigated, focusing on their structures and characteristics, to only then visualize their possible relations.